1989
DOI: 10.1080/08940630.1989.10466510
|View full text |Cite
|
Sign up to set email alerts
|

Rotary Kiln Injection I. An Indepth Study—Liquid Injection

Abstract: A multlfaceted experimental and theoretical program directed toward the understanding of rotary kiln performance Is underway. University, Industry and government participation Is Involved. This paper, the first In a series, presents a general discussion of the overall programmatic goals, followed by a brief description of the sub-programs Including: in-situ measurements from an industrial-scale rotary kiln located at the Louisiana Division of Dow Chemical USA in Plaquemine, Louisiana; laboratory-scale desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 6 publications
3
30
0
Order By: Relevance
“…1 A brief description of the facility and sampling techniques will be presented here for completeness.…”
Section: Experimental Techniques and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A brief description of the facility and sampling techniques will be presented here for completeness.…”
Section: Experimental Techniques and Methodsmentioning
confidence: 99%
“…Figures 2-4 show the sampling positions for each section of the incinerator facility. 1 Based upon results of this run, we concluded that sampling was needed in the upper sections of the kiln. This was accomplished by physically boring an additional access port into the transition section between the kiln and the afterburner so that a vertical distribution at the kiln exit could be obtained.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The data obtained from the three reactors (particle reactor, bed reactor, and kiln simulator) will provide fundamental, transportphenomena parameters so the transients in a full-scale unit can be modeled. In addition, bed mixing is being studied in an ambient temperature, physical-mixing model experiment so that the effects of bed motion may be incorporated into the model.…”
Section: Discussionmentioning
confidence: 99%
“…8 The overall goal of this study is to develop a rudimentary understanding of and a predictive capability for rotary-kiln design. cinerators to define the rate controlling steps, • numerical modeling of the chemical and physical processes that occur during the operation of a rotary kiln incinerator, and • in situ sampling in a full-scale industrial rotary-kiln incinerator to characterize actual incinerator performance.…”
Section: Hot Gasmentioning
confidence: 99%